The influence of depth on the global deep-sea plasmidome - Melany Calderón-Osorno; Dorian Rojas-Villalta; Franck Lejzerowicz; Jorge Cortés; Maria Arias-Andres; Keilor Rojas-Jimenez (Scientific Reports)
Abstract Plasmids play a crucial role in facilitating genetic exchange and enhancing the adaptability of microbial communities. Despite their importance, environmental plasmids remain understudied, particularly those in fragile and underexplored ecosystems such as the deep-sea. In this paper we implemented a bioinformatics pipeline to study the composition, diversity, and functional attributes of plasmid communities (plasmidome) in 81 deep-sea metagenomes from the Tara and Malaspina expeditions, sampled from the Pacific, Atlantic, and Indian Oceans at depths ranging from 270 to 4005 m. We observed an association between depth and plasmid traits, with the 270–1000 m range (mesopelagic samples) exhibiting the highest number of plasmids and the largest plasmid sizes. Plasmids of Alphaproteobacteria and Gammaproteobacteria were predominant across the oceans, particularly in this depth range, which also showed the highest species diversity and abundance of metabolic pathways, including aromatic compound degradation. Surprisingly, relatively few antibiotic resistance genes were found in the deep-sea ecosystem, with most being found in the mesopelagic layer. These included classes such as beta-lactamase, biocide resistance, and aminoglycosides. Our study also identified the MOBP and MOBQ relaxase families as prevalent across various taxonomic classes. This research underscores the importance of studying the plasmidome independently from the chromosomal context. Our limited understanding of the deep-sea’s microbial ecology, especially its plasmidome, necessitates caution in human activities like mining. Such activities could have unforeseen impacts on this largely unexplored ecosystem.